Lethal pulmonary toxicity after autologous bone marrow transplantation/peripheral blood stem cell transplantation for hematological malignancies - Lohr, Frank; Wenz, Frederik; Schraube, Peter; Flentje, Michael; Haas, Rainer; Zierhut, Dietmar; Fehrentz, Dieter; Hunstein, Werner; Wannenmacher, Michael (Radiotherapy and oncology, 1998)
Background and purpose: Retrospective evaluation of the incidence of lethal pulmonary complications (LPC) with special emphasis on interstitial pneumonia (IP) in a large group of patients homogeneously treated with hyperfractionated total body irradiation (HTBI) before autologous bone marrow transplantation (ABMT) or peripheral blood stem cell transplantation (PBSCT) for hematological malignancy. The factors influencing IP are discussed. Materials and methods: Of 260 patients (maximum follow-up 137 months) that were treated with ABMT or PBSCT for hematological neoplasms between 1982 and 1994, 209 patients received HTBI and could be evaluated with respect to lethal pulmonary complications and especially lethal interstitial pneumonia. For most patients (n=155), the HTBI dose was 14.4 Gy (lung dose 9-9.5 Gy) given in 12 fractions over 4 days. Twenty-one patients received a total dose of ≥15 Gy with pulmonary doses of 9-10.5 Gy. Results: The actuarial overall 5-year survival for all 209 patients evaluated was 44±4%, enabling valid evaluation with respect to lethal pulmonary toxicity. The actuarial incidence of all LPC during the first year was calculated as being 8±2%. The actuarial incidence of lethal IP is certainly lower and was estimated to be between 3 and 5% for all patients. The overall treatment-related mortality was 12% in 188 patients that received a total dose of <15 Gy and 24% among the patients treated with a total dose of ≥15 Gy. Conclusion: ABMT/PBSCT, like other transplant modalities without significant graft versus host disease (GvHD), has a low transplant-related mortality, a very small rate of overall LPC and a low incidence of lethal IP after HTBI. Doses up to 14.4 Gy with lung doses of 9-9.5 Gy can be administered safely. For total doses of ≥15 Gy with lung doses of 9-10.5 Gy, the risk of serious transplant-related complications cannot yet be finally assessed but such higher doses should be considered with caution because of the possibility of increasing toxicity in organs other than the lung.